Akwizycja języka obcego w perspektywie studenta filologii: badanie tożsamości narracyjnej studenta w kontekście czasoprzestrzeni i heteroglosii - Werbińska, Dorota (Neofilolog, 2012)
The general aim of this article is to present second language acquisition from the perspective of an English philology student. Taking the position that identity is a relevant concept in language acquisition, it explores how the identity of English philology students, both day and extramural, is constructed in their narratives when drawing on Bakhtin’s notions of „chronotope” and „heteroglossia”.